IOANA STOICESCU. The Acquisition of Tense and Aspect in Romanian. Bucharest: Bucharest University Press, 2013. 287 p. ISBN 978-606-160263-6 (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2025)
This volume is an exploration of the acquisition of tense and aspect in Romanian, reliant on both longitudinal corpora and experimental data. It is based on Ioana Stoicescu’s dissertation, and it provides information on the production of tense/aspect verbal forms in child Romanian, while also looking at associations between grammatical and lexical aspect in child and parental speech. Additionally, it looks into children’s comprehension of some of the main tenses of Romanian: the present, imperfect, and future.